The efficiency of gas injection into low-permeability multilayer hydrocarbon reservoirs - AL-Obaidi, Sudad H; Hofmann, Miel; Khalaf, Falah H.; Alwan, Hiba H. (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The efficiency of gas injection for developing terrigenous deposits within a multilayer producing object is investigated in this article. According to the results of measurements of the 3D hydrodynamic compositional model, an assessment of the oil recovery factor was made. In the studied conditions, re-injection of the associated gas was found to be the most technologically efficient working agent. The factors contributing to the inefficacy of traditional methods of stimulating oil production such as multistage hydraulic fracturing when used to develop low-permeability reservoirs have been analyzed. The factors contributing to the inefficiency of traditional oil-production stimulation methods, such as multistage hydraulic fracturing, have been analysed when they are applied to low-permeability reservoirs. The use of a gas of various compositions is found to be more effective as a working agent for reservoirs with permeability less than 0.005 µm2. Ultimately, the selection of an agent for injection into the reservoir should be driven by the criteria that allow assessing the applicability of the method under specific geological and physical conditions. In multilayer production objects, gas injection efficiency is influenced by a number of factors, in addition to displacement, including the ratio of gas volumes, the degree to which pressure is maintained in each reservoir, as well as how the well is operated. With the increase in production rate from 60 to 90 m3 / day during the re-injection of produced hydrocarbon gas, this study found that the oil recovery factor increased from 0.190 to 0.229. The further increase in flow rate to 150 m3 / day, however, led to a faster gas breakthrough, a decrease in the amount of oil produced, and a decrease in the oil recovery factor to 0.19 Based on the results of the research, methods for stimulating the formation of low-permeability reservoirs were ranked based on their efficacy.